Diversity of the poroid Hymenochaetaceae (Basidiomycota) from the Atlantic Forest and Pampa in Southern Brazil - Campos Santana, Marisa (2015)
A synopsis of the current knowledge about the poroid Hymenochaetaceae from Southern Brazil (States Paraná, Santa Catarina and Rio Grande do Sul) is presented. Fortytwo species belonging to nine genera are reported from the areas surveyed. An annotated, partly illustrated, checklist and identification keys are provided. The new combinations Fomitiporia bambusarum and Fulvifomes rhytiphloeus are also proposed.